Slums and squatters in Asia Cities: a comparative study of Penang and Dhaka - Karim, A.H.M Zehadul; Abdullah, Moha Asri (Serials Publications, 2011)
Slums and squatters1 is predominantly a Third World phenomenon which has become very prominent recently; and as such it has now been increasing at a steady rate ever since. It has often been assumed that the squatters are the marginal population of the land who have been pushed to the unoccupied government and private lands in the urban centers, being victims of continuing rural proleterization. A differential scenario of the squatter settlement pattern in two Asian cities of Penang and Dhaka indicate that although the inhabitants of Dhaka Slums2 are mostly the rural people coming largely from the landless villagers of the peripheral regions throughout the country; the settlers in Penang on the other hand, is comprised of the urban dwellers coming from a multi-ethnic group of people from its surrounding peri-urban centers. Based on our field data from two squatter settlements of Penang and Dhaka, the paper identified basic differentiation in socio-economic characteristics of the settlers of both these groups of people. Based on our empirical data, the paper outlines a comparative situational analysis of the people living there in the slum areas of two rapidly growing cities of Asia. The paper concludes that this differential scenario confirms that squatter settlement has its own peculiarities and characteristics depending on the pace and level of urban development.